Groth and Lampião: Experimental Print Journalism and the Science of Newspapers - Barbosa, Karina Gomes (Brazilian journalism research, 2016)
The current paper is a reflection on the place of the student newspaper in a new Journalism undergraduate course located in a Brazilian countryside region, considering the new curriculum guidelines, in dialogue with Otto Groth’s fundamental concepts of the Science of newspapers. In this sense, we try to demonstrate the constant links between theoretical constructs and experimental praxis of Journalism. For that, we analyze the experience of Lampião, an experimental student newspaper at Ufop, during a semester in 2014, considering it under five categories: periodicity, universality, topicality, publicity and experimentation.